Eyelash Extension Use for Muslim Women from an Islamic Law Perspective - Mitayani, Pawestri (Pascasarjana IAIN Metro, 2024)
The topic of this article is the factors that cause the use of eyelash extensions , especially for Muslim women. What are the impacts that can occur in the use of eyelash extensions , both the impact on oneself and the impact on Islamic law. And what is Islam's view on this phenomenon. Changing something of Allah SWT's creation only for the purpose of beautifying oneself is forbidden. For example, in the use of eyelash extensions . It is forbidden if it is used for the purpose of beautifying oneself, because it can be categorized as changing what has been created by Allah SWT. In addition, the use of eyelash extensions can also have negative impacts on health, namely it can cause irritation and other impacts. The method used in this article is a search for various literature using search engines in the form of Google Scholar. After the article is obtained, an in-depth data analysis is carried out by conducting a study in the form of a literature review.